Therapeutic Effects of Tofacitinib on Pristane-Induced Murine Lupus - Jiayi LIN; Yaqin ZHANG; Meihua WANG; Yang ZHANG; Pin LI; Yingping CAO; Xuwei YANG (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the effectiveness of tofacitinib, a Janus kinase (JAK) 1/JAK3 inhibitor, in treating murine lupus, and also explore 12 related genes downstream of JAK-signal transducer and activator of transcription (STAT) signaling pathways to find the underlying mechanism. Materials and methods: This study was conducted between July 2017 and January 2020. Fifty-seven female BALB/c mice (aging 8 to 10 weeks old; weighing 18 to 20 g) were assigned to a saline control (SC) group and a pristane-induced lupus group. The latter included four groups, namely, pristane control (PC), tofacitinib (T), methylprednisolone (MP), and tofacitinib plus methylprednisolone (T+MP). Animal models of lupus were induced with pristane, whereas SC mice were treated with normal saline. From the 22nd week after induction, each group was given the aforementioned corresponding intervention for 11 weeks. The following variables were tested: serum concentrations of anti-double-stranded deoxyribonucleic acid (anti-dsDNA), interleukin 6 (IL-6), and interferon gamma (IFN-γ); number of regulatory T (Treg) cells; messenger ribonucleic acid levels of forkhead box P3 and 12 related genes downstream of JAK-STAT pathway; and renal impairment. Results: Red swollen joints and proteinuria were first observed in PC after the 12th week. After treatment, T, MP, and T+MP showed relieved red swollen joints and splenomegaly, as well as decreased urine protein, anti-dsDNA, IL-6, IFN-γ, Treg cells, pathological scores, and hyperplasia of mesangial matrix in glomeruli compared with PC. The IFN regulatory factor 7 level was higher in T+MP (p0.05) and MP (p>0.05) than in PC after treatment. The expression of suppressor of cytokine signaling (SOCS) 1 was lower in T (p>0.05), T+MP (p0.05) than in PC. The SOCS3 level was higher in T (p>0.05) and T+MP (p0.05) than in PC. Conclusion: Tofacitinib can ameliorate glomerulonephritis and arthritis in a pristane-induced murine model of lupus. SOCS3 gene may be involved in the therapeutic mechanism of tofacitinib.